Проблеми стимулювання інноваційної діяльності підприємств в Україні - Сєвостьянова, Д. В. (НТУ "ХПІ", 2012)
В статті наведені результати дослідження тенденцій розвитку інноваційної діяльності в Україні; виявлені причини, що стримують цей розвиток, і бар'єри для впровадження інновацій українськими підприємствами; визначені недоліки механізму державного стимулювання інноваційної діяльності підприємств.

In the article, the results of the research of trends in the development of innovative activities in Ukraine are presented; reasons restraining this development and barriers to the implementation of innovations by Ukrainian enterprises are identified; shortcomings in the government policies as to stimulating of innovative activities of enterprises are revealed.
Keywords: інновації; інвестиції; державна політика; податкові пільги; innovations; innovative activities; investment; tax benefit